Measures of reliability in the kinematics of maximal undulatory underwater swimming - Connaboy, C.; Coleman, S.; Moir, G.; Sanders, R. (Medicine & Science in Sports & Exercise, 2010)
Purpose: The purposes of this article were to establish the reliability of the kinematics of maximal undulatory underwater swimming (UUS) in skilled swimmers, to determine any requirement for familiarization trials, to establish the within-subject (WS) variability of the kinematics, and to calculate the number of cycles required to accurately represent UUS performance.